TINDAK TUTUR PERLOKUSI GURU DALAM PEMBELAJARAN BAHASA INDONESIA KELAS XI SMK NEGERI 1 SAWIT BOYOLALI - Insani, Eka Nur; , Dra. Atiqa Sabardhila, M.Hum (2016)
This study reviews the Speech Acts Perlousi Teacher in Indonesian Language Learning Class XI SMK 1 Sawit, Boyolali. This research two purpose; 1) classification of speech acts and effect perlokusi learning Indonesian teachers in class XI SMK Negeri 1 Sawit, Boyolali, 2) the function of speech acts perlokusi Indonesian teacher in class XI SMK Negeri 1 Sawit, Boyolali. This type of research to examine this problem is the methode kualitattif descriptive. A research technique used is the technique involved refer to free skilled, technical notes, and recording technique. Results of the study found that there are four types of speech acts perlokusi ie perlokusi directive speech act, speech act perlokusi expressive, representative perlokusi speech acts and speech acts perlokusi commissive. In a directive speech act perlokusi form; orders, reservations, giving advice.Perlokusi expressive speech acts such as; hatred, pleasure, excitement.Perlokusi representative form of speech acts; affirmation, description, statement of facts, conclusions.Commissive form of speech acts; denial. The results of the analysis in this studyshows the speech acts perlokusi function found on the teachers in learning Indonesian is the function of a competitive and funfunctions.